Employee Engagement at PT. Citra Lampia Mandiri, East Luwu Regency - S, Muh Rizal; Zainal, Henni (Universitas Negeri Makassar, 2022)
Employees who have good work engagements will focus on goals, work actively, always develop abilities and don't give up easily. The purpose of the study was to analyze employee engagement at PT. Citra Lampia Mandiri, East Luwu Regency. The research method used is a quantitative approach. The number of population and samples at PT. Citra Lampia Mandiri, East Luwu Regency are as many as 51 respondents. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique was to perform validity and reliability tests, descriptive statistical analysis, inferential statistical analysis consisting of data normality test, simple linear regression analysis, partial significant test, and determinant coefficients. The result of this research is Employee Engagement at PT. The image of Lampia Mandir Luwu Timur is in the very good category, where the majority of employees who are respondents chose to strongly agree with the statement based on three indicators formulated on the employee engagement variable. With the percentage level of the average score obtained on the results of data processing in the previous chapter, it is in the very very good category.